Prospective Analysis of Hemorrhagic Cystitis and BK Viremia in Allogeneic Hematopoietic Stem Cell Transplantation - Erden Atilla; Can Ateş; Atilla Uslu; Pınar Ataca Atilla; Istar Dolapçı; Alper Tekeli; Pervin Topçuoğlu (Turkish Journal of Hematology, 2020)
Objective: BK virus (BKV) infection has been shown to be related to hemorrhagic cystitis (HC) in allogeneic hematopoietic stem cell transplantation (allo-HSCT). There are conflicting data regarding the association between BKV titers in plasma and clinical disease as well as the risk factors for BKV-related HC. Our aim is to study the risk factors and relationship with plasma BK viral load for development of HC in a prospective analysis. Materials and Methods: We prospectively evaluated 59 patients who received allo-HSCT between 2014 and 2016 by quantitative BK virus polymerase chain reaction (PCR) (Altona Diagnostics, Germany) from blood samples at days 0, 30, 60, and 90 after allo-HSCT. The patients were monitored for signs and symptoms of HC. Results: HC was diagnosed in 22 patients (37%) at a mean of 100 days (range: 0-367 days). In multivariate analysis, the usage of cyclophosphamide (sub-distribution hazard ratio [sdHR]: 7.82, confidence interval [CI]: 1.375-39.645, p=0.02), reactivated CMV (sdHR: 6.105, CI: 1.614-23.094, p=0.008), and positive BKV viremia (sdHR: 2.15, CI: 1.456-22.065, p=0.01) significantly increased the risk of developing HC. Patients with higher viral loads at day 30 and day 60 were diagnosed with more severe HC (p<0.001). Median BK viral loads of >101.5 copies/mL at day 0 (sensitivity 0.727, specificity 0.875), >98.5 copies/mL at day 30 (sensitivity 0.909, specificity 0.875), and >90.0 copies/mL at day 60 (sensitivity 0.909, specificity 0.875) were indicative of HC. Conclusion: Our study showed that administration of cyclophosphamide, CMV reactivation, and BK virus positivity were associated with HC. Plasma BK virus PCR titers at days 0, 30, and 60 after transplant were sensitive tools for predicting clinically proven HC.